2007
DOI: 10.1016/j.surfcoat.2007.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate oxidation on spreading of plasma-sprayed nickel on stainless steel

Abstract: Plasma-sprayed, molten nickel particles (∼ 60 μm diameter) were photographed during impact on oxidized 304L stainless steel surfaces that were maintained at either room temperature or at 350°C. Steel coupons were oxidized by heating them at different temperatures. A fast chargecoupled device (CCD) camera captured time-integrated images of the spreading splat. A two-color pyrometer collected thermal radiation from particles and recorded the evolution of their temperature after impact. Molten nickel particles im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 31 publications
4
32
0
2
Order By: Relevance
“…As the slope of the splat temperature history curve, dT/dt, was defined to be the cooling rate of the splat, the splat cooling rates on heated substrates were remarkable higher than those substrates with room temperature, and increases with substrate heating temperature. Similar result has been proposed while some kinds of micrometer-sized particles were thermally sprayed onto flat substrate surfaces (32)- (34) , which proposed that the investigation on the thermal history of the millimeter-sized free falling droplet is meaningful for understanding the individual thermal sprayed particle. Moreover, the measurement of temperature histories at droplet-substrate interface of Cu splats deposited onto AISI304 substrate kept at various ambient pressures in deposition chamber are shown in Fig.…”
Section: Journal Of Solid Mechanics and Materials Engineeringsupporting
confidence: 76%
See 1 more Smart Citation
“…As the slope of the splat temperature history curve, dT/dt, was defined to be the cooling rate of the splat, the splat cooling rates on heated substrates were remarkable higher than those substrates with room temperature, and increases with substrate heating temperature. Similar result has been proposed while some kinds of micrometer-sized particles were thermally sprayed onto flat substrate surfaces (32)- (34) , which proposed that the investigation on the thermal history of the millimeter-sized free falling droplet is meaningful for understanding the individual thermal sprayed particle. Moreover, the measurement of temperature histories at droplet-substrate interface of Cu splats deposited onto AISI304 substrate kept at various ambient pressures in deposition chamber are shown in Fig.…”
Section: Journal Of Solid Mechanics and Materials Engineeringsupporting
confidence: 76%
“…As reported up to now, effect of dominating process factors on the flattening behavior of an individual splat onto flat substrate surface has been systematically investigated through theoretical (4), (5) , numerical (6)- (8) and experimental methods (9)- (11) in the last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…When metal surfaces are preheated over the transition temperature ( Ref 4,5,10,13,25,26,30,37,38,40,43,52,56,[60][61][62][63][64][65][66] or treated with laser energy densities high enough to modify the oxide layer (Ref 17,20,58), the surface is changed. In addition to desorbtion of adsorbates, the oxide layer composition, thickness and roughness is modified.…”
Section: Substrate Surface Modificationsmentioning
confidence: 99%
“…The underlying cause of the change in splat morphology is not clearly understood. It has been attributed to desorption of gases ( Ref 7,8,11,12), oxidation of the surface ( Ref 3,9), and changes in surface roughness (Ref 1, 3). Jiang (Ref 11) showed that the contact area between splat and substrate is increased and the adhesion is improved on substrates where the adsorbed gas has been removed or reduced.…”
Section: Introductionmentioning
confidence: 99%